Diversity in HLA class I and class II in kidney donors and recipients according to race in KwaZulu-Natal (South Africa) implications for transplantation - Assounga, AGH; Schreiber, V; Allen, V; Anley, D (African Journal of Nephrology, 2013)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">HLA matching of donors and recipients plays a major role in the success of organ transplantation. Race differences inHLA have been reported elsewhere. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Aim: To analyse the diversity of HLA Class I and Class II among kidney donors and recipients according to race. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods: This is a retrospective study of HLA types of renal patients and kidney donors attending the Renal Unitat Addington and Inkosi Albert Luthuli Central Hospitals from 1985 to 2002. Class I HLA typing was done usingserological methods while Class II HLA typing was done using serological or molecular methods at the TissueImmunology Laboratory, South African National Blood Services, Durban, South Africa. Files for 470 individuals werereviewed. There were 143 Blacks, 169 Indians, 88 Whites and 70 Coloureds. All the files were included and analysedaccording to race. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: HLA A locus, 18 distinct antigens were recorded in Black patients. In Indians, 17 antigens were recorded.In Whites, 16 antigens were observed and the most frequent were A2 (29%) and A1 (17%). For the HLA B locus, 29antigens were recorded in Blacks with the two most frequent being B58 (13%) and B44 (12.5%). In Indians, 28 antigenswere recorded. For DR locus 29 distinct antigens were recorded. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Race differences in the profile of HLA types are observed. This may render difficult HLA matchingbetween donors and recipients in organ transplantation.